Factors affecting international students' level of satisfaction towards selected public higher learning institutions in Malaysia - Md Ashraful Azam Khan (Kulliyyah of Economics and Management Sciences, International Islamc University Malaysia, 2016)
Customer satisfaction is one the most vital and key important parts for the success of the firms regardless the type of industry including product and service. Education industry is not an exception as this industry is a provider of services. Here consumers are students who have versatile demands. Malaysia is among the Asian countries which are aiming to be established as extraordinary international educational hub. Consequently, it is important for public higher learning educational institutions to find out the most influential factors those affect the satisfaction of international students. Only by figuring out these factors public higher learning institutions can decide to invest their time, money and effort on the appropriate way. Therefore, this type of research to find the factors affecting international student satisfaction and has become part and parcel for a country like Malaysia. Through the comprehensive review of literatures, it is found that this type of research is already conducted in Malaysia for overall higher learning industry. Especially for private higher learning institutions but very minimal research was conducted concentrating the public higher learning institutions, hence this type of study is still needed as the present literatures are not sufficient to enclose all the facts those are required to be found. As a consequence, through this study it can be expected to get valuable information for the policy makers of this particular area for the ultimate betterment of international student satisfaction in public higher learning education. Quantitative analysis is used in this study. Stratified proportionate random sampling technique is applied to select the respondents. Total 200 respondents were involved from the selected public higher learning institutions. SPSS statistical analysis is applied to measure the relationships between and among the constructs.Based on several statistical and scientific researches and the results found by the study is that, international students in Malaysian public higher learning institutions treat three factors mainly Facilities, Teaching quality and E-learning significant while connecting them with their satisfaction level. Future research is suggested in order to find out the in-depth information about the international students from other public higher learning institutions and different geographic region regarding their satisfaction factors, facts in public higher learning institutions by using mixed method or involving qualitative method of study beside quantitative method.